Awareness of sustainable manufacturing practices in Malaysian manufacturers - Jafartayari, Saman (2010)
This research is targeted at investigating all aspects of sustainable manufacturing awareness and practice level based on the 6R concept. Malaysian manufacturers have been assessed and categorized into electrical and electronics industries, engineering supporting and machinery industries, and other industries. There were four main objectives determined for this study: determining the level of awareness about the sustainability concept among Malaysian manufacturers, determining the companies’ practices related to sustainability and proposing improving actions contributing to the sustainability enhancement of products and processes. For data collection, online questionnaire was used and there are six main sections use to help analyze the factors and find the correlations within the factors and their correlation with general information of the company and the person in charge of questionnaire. Six main sections that involved are general information, sustainability concept, three issues of society, environment and economics, energy saving and waste tracking methods, reusing- recycling - remanufacturing, life cycle activities and suggestions. General information and the conceptual questions were analyzed with descriptive analysis. Likert scaled questions were analyzed with mean score and correlation analysis (regression and ANOVA), Fisher test (for StD differences) and T-test (for mean differences). Lastly the survey results show that the level of awareness on sustainable manufacturing has direct relationship with the sustainable manufacturing practices. The sustainable awareness and practices related to most of the Rs (6Rs) is at a satisfactory level while in some of the Rs the practice levels seem to need attention.